UPAYA SEKOLAH DALAM PELESTARIAN NILAI-NILAI PANCASILA MELALUI PROGRAM EKSTRAKURIKULER DI MIN 13 ACEH TIMUR - Razika Autari, Siti; Ayudia, Inge; Mahlianurrahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The preservation of Pancasila values is essential in shaping national character amid the challenges of globalization and shifts in the mindset of the younger generation. Schools play a strategic role in instilling these values, one of which is through extracurricular activities. Objective: This study aims to examine the school's efforts to preserve Pancasila values through extracurricular programs, the implementation of Pancasila values by students, and the obstacles faced by the school in integrating these values at MIN 13 Aceh Timur. Methods: This research applied a qualitative descriptive approach at MIN 13 Aceh Timur from November 1, 2024, to July 1, 2025. Research informants consisted of the principal, teacher advisors, and students. Data were collected through observation, interviews, and documentation, and then analyzed using data reduction, data display, and verification. Results: The findings indicate that the school integrates Pancasila values into Scouting (Pramuka), junior doctors (dokter kecil), sports, dance arts, and religious activities. These activities foster discipline, responsibility, cooperation, social concern, tolerance, and religiosity among students. Teachers serve as facilitators in shaping students' moral, social, and spiritual attitudes. Pancasila values are reflected in students' independence, discipline, mutual cooperation (gotong royong), and respect for differences. The obstacles faced by the school include limited teacher competence, scheduling constraints, diverse student characters, external environmental influences, and limited supporting facilities for extracurricular activities.